EFFECT OF FEED CHANGE OF Artemia sp WITH Tubifex sp TO GROWTH AND SURVIVAL OF TAMBAQUI(Colossoma macropomum) MAINTAINED BY WATER RECIRCULATION SYSTEM - Purnomo, Agus; Aryani, Netti; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtrakThis research was conducted from April to June 2017 at Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, University of Riau. The aim of this research is to know the effect of natural feed change of Artemia sp with Tubifex sp to growth and survival of fresh tambaqui (Colossoma macropomum) which maintained by water recirculation system. The method used in this study is an experimental method with Completely Randomized Design (RAL) with one factor, five treatments and three repetitions. The treatments in this study were P1 is giving of Artemia sp for 7 days and Tubifex sp for 33 days, P2 is giving of Artemia sp for 14 days and Tubifex sp for 26 days, P3 is giving Artemia sp for 21 days and Tubifex sp for 19 days, P4 is giving of Artemia sp for 40 days and P5 is giving of Tubifex sp for 40 days. Parameters measured is absolute weight growth, absolute long growth, daily weight growth rate and survival. The results showed that the best change of feed treatment was on P1 with absolute weight growth was 3.17 grams, absolute long growth was 4.87 cm, daily weight growth rate was 18.83 % / day and the survival rate was 97.78%.Keywords: Tubifex sp, Artemia sp, growth and survival of (Colossoma macropomum)